The Philosophy of Life of The Alor Regency Community: A Literature Analysis of Cultural Values in Early Childhood Care Practices - Wollo, Stevanya Lucia Wety (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
Cultural identity plays an important role as a binding element of society as well as the basis for character building of the next generation. This research aims to explore the Alorese philosophy of life and its contribution to parenting and character building. A qualitative approach was used with literature analysis, involving data sources such as government reports, journals, books and articles relevant in the last 10-15 years. Data were analyzed through a process of coding, classification, and thematization. The results revealed the values of 'Ite Kakang Aring' (we are all brothers and sisters) and 'Tara Miti Tomi Nuku' (different but one) as the foundation of brotherhood, tolerance, and social harmony manifested through traditions such as the Lego-Lego dance and the kinship system. The implication is that cross-sector collaboration is needed to integrate these cultural values into formal, non-formal and family education programs in order to form a generation of characters who respect diversity